(untitled) (Journal of Economics, Law and Society, 2025)
This paper examines how banking sector concentration and profitability relate to non-performing loans (NPLs) in a broad cross-country setting. Using an unbalanced panel of 93 countries over 2000-2020, it combines system-level data on the ratio of bank non-performing loans to gross loans, the asset share of the three largest banks (concentration), and the post-tax return on assets (ROA) of the banking sector. The empirical strategy proceeds in two steps. First, descriptive statistics and simple correlations document basic patterns in NPLs, concentration and profitability, including systematic differences between advanced and other economies. Second, a set of linear regressions is estimated with NPLs as the dependent variables: pooled ordinary least squares models, panel specifications with country fixed effects and year dummies, and pooled interaction models that allow coefficients to differ between advanced and other country groups. The results indicate a robust, economically meaningful negative association between profitability and NPLs across specifications: higher ROA is consistently linked to lower NPL ratios. By contrast, banking sector concentration plays a more nuanced role. In pooled regressions, concentration is only weakly related to NPLs, but in fixed-effects models increases in concentration within countries over time are associated with moderately higher NPLs. Advanced economies exhibit persistently lower NPL ratios than other economies even after conditioning on concentration and profitability, while the marginal effects of these variables appear broadly similar across groups. Overall, the findings highlight the importance of sustained profitability for asset quality and suggest that greater concentration does not automatically translate into lower credit risk.